Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

This is the question:

Use the integral test to determine the convergence of $\sum_{n=1}^{\infty}\frac{1}{1+2n}$.

I started by writing:

$$\int_1^\infty\frac{1}{1+2x}dx=\lim_{a \rightarrow \infty}\left(\int_1^a\frac{1}{1+2x}dx\right)$$

I then decided to use u-substitution with $u=1+2n$ to solve the improper integral. I got the answer wrong and resorted to my answer book and this is where they went after setting $u=1+2n$:

$$\lim_{a \rightarrow \infty}\left(\frac{1}{2}\int_{3}^{1+2a}\frac{1}{u}du\right)$$

And the answer goes on...

What I can't figure out is where the $\frac{1}{2}$ came from when the u-substitution began and also, why the lower bound of the integral was changed to 3.

Can someone tell me?

share|cite|improve this question
up vote 3 down vote accepted

$$u=1+2x\Longrightarrow du=2dx\Longrightarrow dx=\frac{1}{2}du$$

Remember, not only you substitute the variable and nothing more: you also have to change the $\,dx\,$ and the integral's limits: $$u=1+2x\,\,,\,\text{so}\,\, x=1\Longrightarrow u=1+2\cdot 1 =3$$

share|cite|improve this answer
Oh yes, I forgot that you have to change the limits of integration when u-substituting to the u-substitution limits of integration. – ODP Aug 28 '12 at 16:07

You have $\int_{1}^{\infty}{\frac{1}{1+2n}\:dn}=\lim_{a\to\infty}\left(\int_{1}^{a}{\frac{1}{1+2n}\:dn}\right)$. Using the substitution you mentioned $u=1+2n$, we have our lower bound as $u(1)=1+2(1)=3$ and our upper bound as $u(a)=1+2(a)=1+2a$.

We also have $\frac{du}{dn}=2\implies dn=\frac{du}{2}$, therefore we have:


Taking our previous limit, we have:


Which is what you have in your answer book.

share|cite|improve this answer

Let $1 + 2x = u$ then $du = 2 dx \implies du = {1 \over 2} dx$

$x $ goes from $1$ to $\infty$, since we are using new variable $u$ here, it would have different bound. When $x \rightarrow \infty$, $ u \rightarrow \infty$ and when $x = 1$, $ u = 1 + 2 \cdot ( 1) = 3 $, so $u$ goes from $3$ to $\infty$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.